Modernity. The Fundamentalist Dimension - Mouzelis, Nicos (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2016)
The basic argument in this paper is that fundamentalism is modern not only or primarily in terms of the material and organizational technologies that it uses: it is also modern in terms of its basic sociostructural features, features which have an elective affinity with the unique characteristics of modernity. Choosing Islamic fundamentalism as an example, I will also try to see how the sociostructural level of the phenomenon relates, not only to the cultural but also to the psychodynamic/psychoanalytic level.